Legal Analysis on the Fatwa of Sharia National Council on Rahn: Between Legal Philosophy and Its Implementation in Indonesian Sharia Pawnshop - Fedro, Alfarid; Lahuri, Setiawan bin; Ghozali, Mohammad (IAIN Samarinda, 2019)
The function of Sharia Financial Institutions (SFI) is to provide the easiness for the needs of the community in sharia-compliant funding. One of them is Pegadaian Syariah (sharia pawnshop), which offers the pawning (rahn) contract as one of the sharia-compliant quick funding solutions. The National Sharia Council (NSC) realized the need to issue a fatwa on the guidelines on rahn as a form of response to the needs of the community in various SFI products. However, this fatwa contains biased meaning against the concept the rahn which is obscurely implemented between dain and qardh in some SFI contracts. Therefore, this study tries to analyze the DSN Fatwa NO. 25/DSN-MUI/III/ 2000 and DSN Fatwa NO. 26/DSN-MUI/III/2000 concerning rahn between legal philosophy and its implementation in sharia pawnshops from the perspective of Fiqh Muamalah. The result of this study emphasizes that it is necessary to include in this fatwa a legal philosophy underlying reason for pawning (rahn) decision, whether it is debt (dain) caused by buying-selling/trading (bai') or due to money loan debt (qardh). This basis will explain the sharia-compliant boundaries of the implementation of the rahn contract in SFI, especially in sharia pawnshops which still makes qardh the basis for the realization of rahn implementation.Keywords: sharia pawnshops, rahn, qardh, DSN Fatwa NO. 25/DSN-MUI/III /2002 and DSN Fatwa NO. 26/DSN-MUI/III/2002.